STUDI MIKROSTRUKTUR SERBUK NANO KARBON HASIL PROSES BALL MILLING DENGAN METODE (SCANNING ELECTRON MICROSCOPY) SEM - Muhammad Ainur Rosiqin, Muhammad; Nataria Fitri Ganda, Andita; Puspitasari, Dewi (Jurnal Rekayasa Mesin, 2025)
This study investigates the microstructural characteristics and elemental composition of nano carbon powder produced through a ball milling process using Scanning Electron Microscopy and Energy Dispersive X-Ray (SEM-EDX). The milling process was conducted using a horizontal ball mill with a milling time of 6 hours and a rotational speed of 140 rpm, selected based on the optimal parameters obtained from prior analysis. Carbon material was milled using a combination of zirconia balls with various diameters to enhance the comminution efficiency. The results indicate that the ball milling process significantly reduced the particle size to the nanoscale, achieving a size reduction value of 89.8%. SEM observations revealed that the carbon particles exhibited thin, flaky, and irregular morphologies, indicating the occurrence of mechanical exfoliation during milling. EDX analysis confirmed that carbon (C) was the dominant element, accompanied by minor elements such as O, Mn, Fe, and Zn, which are attributed to mechanical interactions and sample preparation processes. Overall, the milling parameters of 6 hours and 140 rpm were found to be effective in producing nano carbon powder with favorable microstructural characteristics for potential carbon-based material applications.